Etiology of Fever in Neonates: Is It Just Due to Infection? - Baysal, Bora; Baysal, Bahar Toklu; Calkavur, Sebnem; Atlihan, Fusun (Journal of Pediatric Infectious Diseases, 2018)
Objectives Fever is an abnormal elevation of body temperature that occurs as part of a specific biologic response that is mediated and controlled by the central nervous system. In neonates, it may indicate a serious underlying disease. With this study, we aimed to investigate the causes of fever in neonates.Methods Medical charts were reviewed retrospectively for all term newborn infants treated at the Behcet Uz Children's Hospital between 31 December 2007 and 31 December 2009 who subsequently developed fever during their first 28 days. The history of the newborn included type of feeding (formula or breast); weight loss, environmental temperature, and symptoms of infection (lethargy-poor suck, irritability, vomiting, abdominal distention, respiratory distress, and diarrhea) were noted; and physical examination also established. The standard laboratory workup for febrile infants included blood, cerebrospinal fluid, urine and stool cultures, blood count, C-reactive protein, and analysis of serum electrolytes.Results It was determined that the most admissions were made in summer and most frequently in July. The most frequent cause of fever was infection, followed by unexplained fever and dehydration. Clinical sepsis was more frequent than proven sepsis. Risk for neonatal infection was increased by normal spontaneous vaginal birth, whereas the risk for dehydration was increased by cesarean section.Conclusions Environmental factors and dehydration may also be a factor in the newborn who is admitted for fever. But given our results, a newborn with a complaint of fever should be managed as an infection until proven otherwise.
Keywords: neonatal; fever; sepsis; dehydration